2000
DOI: 10.1021/jf991091q
|View full text |Cite
|
Sign up to set email alerts
|

Use of Heme Iron Concentrate in the Fortification of Weaning Foods

Abstract: The purpose of this study was to evaluate the technological feasibility of fortifying homogenized weaning food with a porcine heme concentrate. The stability of iron and the organoleptic qualities of two infant weaning foods (a commercial homogenized nonfortified weaning food, NFWF, and the same food fortified with 0.5% of porcine heme concentrate, FWF) were tested throughout 8 months of storage at room temperature and at 37 degrees C. Heme iron decreased with storage time; however, the proportion of this high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…Colour varied between yellow and red with their different hue values, since only positive values of a* and b* were obtained. This is in agreement with the results reported by Martı´nez-Gracia´et al (2000). The highest values of L*, b*, h and C* corresponded to FC 4.5 and FC + F 4.5 extracts, while the lowest ones corresponded to P + F 9.5 and BHC 9.5 .…”
Section: Average Pclsupporting
confidence: 93%
See 1 more Smart Citation
“…Colour varied between yellow and red with their different hue values, since only positive values of a* and b* were obtained. This is in agreement with the results reported by Martı´nez-Gracia´et al (2000). The highest values of L*, b*, h and C* corresponded to FC 4.5 and FC + F 4.5 extracts, while the lowest ones corresponded to P + F 9.5 and BHC 9.5 .…”
Section: Average Pclsupporting
confidence: 93%
“…On the contrary, as iron content decreases, higher values of b* is observed and the colour tend to be more yellowish. This is in agreement with the results reported by Martı´nez-Gracia´et al (2000). They found that the addition of porcine heme iron in weaning foods produced a decrease of the parameters b*, h and C*, in comparison with the control.…”
Section: Determination Of Iron Content In the Extracts Obtained At DIsupporting
confidence: 93%
“…Bovine Hb has been used as a source of iron to fortify infant cereals 15,16 , toddler weaning foods 18 , biscuits 14 and cookies/cakes for the school-aged population 17 . The impact of a haem-based iron preparation on anaemia in infants 15,16 and juvenile populations was investigated in Chile 17 .…”
Section: Discussionmentioning
confidence: 99%
“…The protein content of red blood cells (or blood cells) of the whole blood is 34–38% [1]. The blood cells (BCs), which are obtained by removing the plasma from whole blood, mainly contain the hemoglobin and ferrous in the form of heme-Fe with high bioavailability [3, 4]. The spray-dried blood cells are high in protein and have a favorable AA profile [5].…”
Section: Introductionmentioning
confidence: 99%